BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Plant Viruses as Molecular Pathogens. Edited by J.A. Khan and J. Dijkstra, Food Products Press, an imprint of The Haworth Press, Inc., New York, USA 2002, 537pp Diseases of Vegetable Crops, Editors : V.K Gupta and Y.S. Paul, Kalyani Publications, New Delhi, 2001, 277 pp, Price Rs. 250 Fundamentals of Plant Bacteriology, Authors Jayashree Jayaraman and Jeevan Prakash Verma; Publisher; Kalyani Publishers, Ludhiana, New Delhi, Noida (U.P.) Hyderabad, Chennai, Kolkata, Cuttack, 2002, 129 pp.